Comparison of simultaneous saccharification and fermentation with LPMO-supported hybrid hydrolysis and fermentation - Tang, Chaojun; Cavka, Adnan; Bui, Mai; Jönsson, Leif J. (Frontiers in Bioengineering and Biotechnology, 2024)
Enzymatic saccharification is used to convert polysaccharides in lignocellulosic biomass to sugars which are then converted to ethanol or other bio-based fermentation products. The efficacy of commercial cellulase preparations can potentially increase if lytic polysaccharide monooxygenase (LPMO) is included. However, as LPMO requires both a reductant and an oxidant, such as molecular oxygen, a reevaluation of process configurations and conditions is warranted. Saccharification and fermentation of pretreated softwood was investigated in demonstration-scale experiments with 10 m 3 bioreactors using an LPMO-containing cellulase preparation, a xylose-utilizing yeast, and either simultaneous saccharification and fermentation (SSF) or hybrid hydrolysis and fermentation (HHF) with a 24-hour or 48-hour initial phase and with 0.15 vvm aeration before addition of the yeast. The conditions used for HHF, especially with 48 h initial phase, resulted in better glucan conversion, but in poorer ethanol productivity and in poorer initial ethanol yield on consumed sugars than the SSF. In the SSF, hexose sugars such as glucose and mannose were consumed faster than xylose, but, in the end of the fermentation >90% of the xylose had been consumed. Chemical analysis of inhibitory pretreatment by-products indicated that the concentrations of heteroaromatic aldehydes (such as furfural), aromatic aldehydes, and an aromatic ketone decreased as a consequence of the aeration. This was attributed mainly to evaporation caused by the gas flow. The results indicate that further research is needed to fully exploit the advantages of LPMO without compromising fermentation conditions.